Правовий статус українських громадських організацій на Волині (1918–1939 рр.) - Булавіна, С.; Bulavina, S. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено юридичні підстави діяльності українських громадських організацій Волині міжвоєн- ного періоду. Проаналізовано характерні особливості українських громадських організацій, зокрема регіональ- них підрозділів «Просвіти», «Рідної школи», Товариства імені Лесі Українки. Досліджено основні статутні засади їхньої діяльності.In the article the legal basis of Ukrainian public organizations of Volyn region in the interwar period is investigated. Characteristics of Ukrainian public organizations are analyzed and main statutory provisions are proved. It is shown that after the World War I nation-states appeared instead of powerful empires and a new political order was formed. The principle of selfdetermination was universally recognized, but not always used. Considerable attention is given to the newly formed Polish state, with the population of 27 million people, including more than 5 million Ukrainians. The government conducted the anti-Ukrainian policy. Ignoring the needs of the Ukrainians, the Polish government has acted as if it were native Polish lands, by subjecting the political, cultural and economic life of Western Ukraine its own interests.
Legal Status of Ukrainian Public Organizations in Volyn (1918–1939).
Keywords: правовий статус; українські громадські організації; українсько-польські відносини; законодавство; Волинь; legal status; Ukrainian public organizations; ukrainian-polish relations; statute; legislation; Volyn